Response of growth and myogenic factors in human skeletal muscle to strength training - Liu, Y.; Heinichen, M.; Wirth, K.; Schmidtbleicher, D.; Steinacker, J. M. (British Journal of Sports Medicine, 2008)
Objective: To investigate the response to different strength training techniques of growth and myogenic factors in human skeletal muscle, with particular emphasis on satellite cell (SC) activation.